Analysis of Constraints on the Implementation of the Independent Curriculum in PAUD Level Mobilizing Schools in Situbondo District - Fathor Rakhman; Miftahus Surur (Didaktika: Jurnal Kependidikan, 2024)
This study uses a qualitative research approach to discuss the obstacles to the implementation of the independent curriculum in PAUD-driving schools in Situbondo Regency. Qualitative research methods were used to collect data through in-depth interviews with PAUD teachers in kindergartens in Situbondo, including Nurul Anshor Islamic Kindergarten, DWP 1 Besuki Kindergarten, DWP 1 Asembagus Kindergarten, Kartika IV-71 Kindergarten, Nurul Huda Kindergarten, DWP 1 Jatibanteng Kindergarten, and Hasyim Asy'ari Kindergarten, direct observation in schools that were the object of research, and document analysis related to the implementation of the independent curriculum. The results of this study show obstacles. These obstacles include differences in students' learning styles and initial abilities, adaptation to the "All Day Without Mom" program, the use of less attractive worksheets, limited facilities and infrastructure, limited understanding of IT teachers, limited budget, and difficulties in preparing school documents. The recommendations proposed to overcome these obstacles are teacher training and support, cooperation with parents, development of interesting learning materials, improvement of facilities and infrastructure, IT training for teachers, efficient budget management, and support in the preparation of school documents. By implementing these recommendations, it is hoped that PAUD schools in Situbondo District can improve the effectiveness of the implementation of the independent curriculum and the quality of education for PAUD children holistically and sustainably.